A theory of spin vortices in a physical vacuum consisting of quantum oscillators - Boldyreva, Liudmila Borisovna (Cambridge Scholars Publisher, 2021)
This book will be of interest not only to physics scholars who are studying the theoretical aspects of quantum mechanics, electromagnetism, superconductivity and superfluidity, but also to the more general reader. It explores the action of biologically active substances and low-intensity physical factors in ultra-low doses on biological systems, particularly the action of medicinal remedies in ultra-low doses (homeopathy), influence of the color and form of ambient bodies, and the so-called Twin Correlation.